Static VAR compensator for improving voltage profiles and transmission losses: Case study in Batam. (August 2019) - Yunus, S; Rahmi, Y I; Nazir, R; Aulia,; Dinata, U G S
Abstract: Batam has companies engaged in the industry and requires a good quality of electrical power supply. FACTS Devices such as SVC can be mounted to absorb/produce reactive power to control the flow of power to the electrical system of Batam to solve the voltage drop in power transmission in Batam. Newton Raphson method is one method of power flow that is available in the ETAP to simulate the Batam electrical system before and after the addition of the SVC. The Simulation result suggested installing an SVC on bus 20 kV GI Tj. Uban with generated QC and QL values are 15, 699.2 kVAR and 31, 358.18 kVAR. With these values, the voltage can be improved about 1.132 kV with an active power difference of 6 kV.